Simulation study on converter transformer windings stress characteristics under harmonic current and temperature rise effect - Jing Xu; Jian Hao; Ning Zhang; Ruijin Liao; Yun Feng; Wenlong Liao; Huanchao Cheng (International Journal of Electrical Power & Energy Systems)
High-frequency harmonic current leads to temperature increases and uneven stress distribution within ultra-high-voltage (UHV) converter transformer windings. This paper presents a simulation study that explores the stress distribution characteristics in UHV converter transformer windings, taking into account the thermal effects of harmonic current. The research developed a two-dimensional (2D) refined simulation model integrating electromagnetic, thermal-fluid, and solid mechanics fields to analyze the temperature distribution patterns influenced by harmonic currents. The study investigated the influence of temperature rise on the stress distribution within the windings, analyzing the effects of harmonic current content and frequency on the maximum stress values. Finally, the study proposed and validated a novel winding stress calculation model that incorporates the effects of harmonic current and their associated temperature rise. The results demonstrate that hotspot temperatures on both the grid and valve side windings increase as a power function of harmonic current content and exponentially with frequency. Following the inclusion of thermal rise effects, the stress in the grid-side and valve-side windings shifts towards the oil channels between the two windings and also spreads from the hotspot temperature regions to the central regions of the windings. Maximum stress changes under varying harmonic frequencies follow a power function growth pattern. Stress values from the proposed model, considering thermal effects, deviate by less than 5% from those calculated using multi-field coupling simulation. This study provides essential guidance for the design and maintenance of UHV converter transformer windings under new power system operating conditions.